Une éthique minimale est-elle compatible avec l'éducation ? - Jean-Pascal Alcantara (Nantes Université, 2014)
Within the educational world, the mainstream moral philosophy originates in Kantian even Levinassian roots. As an alternative way, Ruwen Ogien's minimalist ethics just begins to rise. Denouncing each failure of the liberal state to respect its obligation of axiological neutrality, such a project doesn't particularly seem to be suited for the educators' use. Indeed it is not obvious whether its leading principles (no harm, equal consideration, neutrality) are likely to determine a strong enought morality convenient with the finalities of education. However, in the following, a minimalistic outlook might turn out to be no less compatible with an overidding clause about education than Mill's utilitarianism. Given a context of democratic pluralism, a citizenship education, understood from the less we can share, doesn't look as a nonsensical idea. Further we reply to some objections in order to succeed in harmonizing moral commitments (even minimalistic) with the main outcomes of the political thought drawn from the theory of justice.